Immune complex type crescentic glomerulonephritis and ANCA-positivity in a nine-year-old girl - Soylu, Alper; Kavukçu, Salih; Turgut, Canan Şule; Türkmen, Mehmet; Sarıoğlu, Sülen (The Turkish Journal of Pediatrics, 2002)
We report a nine-year-old girl who presented with the clinical and laboratory findings of rapidly progressive glomerulonephritis. She was found to be positive for both pANCA and cANCA. However, renal histopathology revealed immune complex type of crescentic glomerulonephritis. Thus, although testing for ANCA is an important tool in the prediction of the subtype of crescentic glomerulonephritis, a renal biopsy is still required to establish the diagnosis.